2022
DOI: 10.1111/nan.12833
|View full text |Cite
|
Sign up to set email alerts
|

Delineating selective vulnerability of inhibitory interneurons in Alpers' syndrome

Abstract: Aims: Alpers' syndrome is a severe neurodegenerative disease typically caused by bi-allelic variants in the mitochondrial DNA (mtDNA) polymerase gene, POLG, leading to mtDNA depletion. Intractable epilepsy, often with an occipital focus, and extensive neurodegeneration are prominent features of Alpers' syndrome. Mitochondrial oxidative phosphorylation (OXPHOS) is severely impaired with mtDNA depletion and is likely to be a major contributor to the epilepsy and neurodegeneration in Alpers' syndrome. We hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 91 publications
6
13
0
Order By: Relevance
“…One study reported an association between the loss of PV+ neurons in the entorhinal cortex with neuropathological amyloid-β and tau burden [ 134 ]. Loss of PV expression has been reported in DLB post-mortem hippocampal tissue [ 12 ], and in primary visual cortical areas [ 135 ], which is similar to our observations in PMDs [ 18 , 19 ], while others found no changes [ 136 ]. However, many factors including the brain region studied, sex and disease stage could all contribute to the differences reported.…”
Section: Parvalbumin Neuron Deficits In Alzheimer's Disease and Demen...supporting
confidence: 92%
See 3 more Smart Citations
“…One study reported an association between the loss of PV+ neurons in the entorhinal cortex with neuropathological amyloid-β and tau burden [ 134 ]. Loss of PV expression has been reported in DLB post-mortem hippocampal tissue [ 12 ], and in primary visual cortical areas [ 135 ], which is similar to our observations in PMDs [ 18 , 19 ], while others found no changes [ 136 ]. However, many factors including the brain region studied, sex and disease stage could all contribute to the differences reported.…”
Section: Parvalbumin Neuron Deficits In Alzheimer's Disease and Demen...supporting
confidence: 92%
“…Stroke-like episodes in PMDs are subacute-onset evolving encephalopathic episodes associated with neurological and/or psychiatric symptoms, which are hypothesised to be driven by focal seizure activity [ 52 , 59 , 60 ]. Although the mechanisms underpinning epilepsy in PMDs have not been fully elucidated, there is mounting evidence demonstrating dysfunction of inhibitory interneurons and glial cells is implicated in neuronal hyperexcitability and seizure generation [ 17 , 18 , 61 , 62 ].…”
Section: Inhibitory Parvalbumin Neuron Involvement In Primary Mitocho...mentioning
confidence: 99%
See 2 more Smart Citations
“…Our study not only revealed the loss of neurons but also highlighted the presence of astrocyte activation and reactive gliosis in patient‐derived organoids. The observed astrocyte activation is particularly significant as it has been shown in our study [ 26 ] and previous research [ 34–36 ] to be associated with neuronal toxicity and may contribute to the neural loss observed in POLG‐related disorders. Astrocytes play crucial roles in supporting neuronal function and maintaining brain homeostasis.…”
Section: Discussionsupporting
confidence: 68%